Morphological description and DNA barcodes of adult males of Tanytarsus heliomesonyctios Langton, 1999 (Diptera, Chironomidae) in northeast of Russia - Orel, Oksana V.; Semenchenko, Alexander A. (Zootaxa, 2019)
An illustrated morphological description of the adult males of Tanytarsus heliomesonyctios Langton, 1999, is provided for the first time. The males were found in mountain lakes Bolshoi Darpir (Momsky District of the Republic of Sakha (Yakutia)) and Momontai (Susumansky District of the Magadan Region), located in the Kolyma River basin. Females, pupae and larvae of T. heliomesonyctios was previously described from Spitsbergen, Jan Mayen (Norway) and Ellesmere Island (Arctic Canada), and considered parthenogenetic. Tanytarsus heliomesonyctios is here for the first time noted for the fauna of Russia. Comparison of DNA barcodes shows high K2P nucleotide distances (1.7%) between the sexual populations (Norway and Russia) and the parthenogenetic populations (Svalbard and Canada). In the Bayesian tree, the COI- sequences from adult males group as sister to a strongly supported clade of sequences from parthenogenetic populations. This apparently indicates a single origin of parthenogeneticity, perhaps due to extreme environmental conditions.